Unemployment insurance in the United States : analysis of policy issues - O'Leary, Christopher J.; Wandner, Stephen A. (Kalamazoo, Mich. : W.E. Upjohn Institute for Employment Research, 1997)
Discusses the unemployment insurance system in which programmes are operated by each state within the minimum standards established by the federal government.
/ Phillip B. Levine -- Trends in unemployment benefit financing / Mike Miller, Robert Pavosevich, Wayne Vroman -- Fraud, abuse, and errors in the unemployment insurance system -- The role of the employment service / David E. Balducchi, Terry R. Johnson, R. Mark Gritz -- Intersection of unemployment insurance with other programs and policies / Walter S. Corson -- Federal-state relations / Thomas E. West, Gerard Hildebrand --Unemployment compensation in the group of seven nations / James R. Storey, Jennifer A. Niesner -- Summing up / Christopher J. O'Leary, Stephen A. Wandner.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Unemployment insurance -- United States; Unemployment insurance -- United States -- History; Unemployment insurance -- Government policy -- United States -- History; Assurance-chômage -- États-Unis.; Assurance-chômage -- États-Unis -- Histoire; Assurance-chômage -- Politique gouvernementale -- États-Unis -- Histoire; POLITICAL SCIENCE -- Public Policy -- Social Security; Unemployment insurance; Unemployment insurance -- Government policy; United States; Arbeitslosenversicherung; Politik; Aufsatzsammlung; USA; Werkloosheidsverzekering; Overheidsbeleid; Labor & Workers' Economics; Business & Economics; unemployment benefit; payment of benefits; social security financing; regional level; national level; unemployed; long term unemployed; employers participation; contributions; taxation; payment system; eligibility; duration; earnings replacement rate; work incentive; employment policy; employment service; statistical table; Canada; France; Germany; Italy; Japan; United Kingdom of Great Britain and Northern Ireland; USA; prestations de chômage.; paiement des prestations; financement de la sécurité sociale; niveau régional.; niveau national; chômeurs.; chômeur de longue durée.; participation des employeurs; cotisations; fiscalité; système de paiement; conditions d'ouverture des droits; durée.; taux de remplacement; incitation au travail; politique de l'emploi.; service de l'emploi.